Factors Affecting Value Co-Creation Behavior for Social Enterprises in Retail Sector - 윤성준; 김희연 (Journal of distribution science, 2024)
Purpose: In view of increased social awareness of today’s consumers, it is very important to understand how retail customers perceive their sense of social responsibility. This study aims to explore the decision processes of university students that affect the patronage of social enterprises in retail sector. Research design, data and methodology: This study proposes and tests whether and how social network traits, firm’s image, and perceived trustworthiness serve as predictors of value co-creation behavior specific to two different industries (social enterprises and regular firms) operating in retail sector of South Korea. This study incorporated theoretical premise of value co-creation to verify the structural relationships among the predictors of value co-creation. Results: The result demonstrates that social network and firm’s image both significantly influence consumers’ value co-creation behavior. The study further found that the firm’s image is overall more effective for eliciting consumers’ value co-creation behavior than social network traits. Conclusions: As the result of comparing the industry type (social enterprises vs. regular firms), the study confirmed a meaningful difference such that consumers indicated greater impact of firm’s image on value co-creation for social enterprises than for regular firms. The findings are expected to provide useful industrial insights for the management of social enterprises. KCI Citation Count: 1